The rice soils of cambodia. II. Statistical discrimination of soil properties by the cambodian agronomic soil classification system (casc) - Oberthür, T.; Dobermann, A.; White, P. (Wiley, 2000)
. A novel agronomic system of soil classification for managing rice soils in Cambodia (CASC) was developed recently. It integrates local knowledge about the soil with its conceptual and taxonomic understanding by soil scientists. Using quantitative soil survey data we evaluated the agronomic efficacy of the classification system. Although the CASC is based on simple field criteria it explained 25 to 44% of the variation in soil prop‐erties relevant for agronomic decision making. It failed, however, to differentiate soil types based on pH (6% of variances explained). Despite its simplicity it performed as well or better than the most widely used soil map in Cambodia (Crocker, 1962), and unlike this small‐scale soil map it allows classification on a field‐specific basis. The average values of soil properties were often significantly different between groups. Organic carbon, clay content and plant available magnesium and calcium contributed most to the discrimination of CASC soil groups. The predictive accuracy when allocating new samples on the basis of quantitative survey data to soil groups of the CASC was 50% to 100%, except for soil groups Kein Svay (0%) and Kampong Siem (20%). The CASC is valuable for managing Cambodian rice soils and may also be used for up‐scaling and mapping of soil information.